Management Strategy of Mangrove Ecosystem in Siak Regency, Riau Province, Indonesia - Trisla Warningsih; Kusai Kusai; Lamun Bathara; Zulkarnain Zulkarnain; Tomi Ramadona; Deviasari Deviasari (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Coastal ecosystems on small islands have a large enough pressure to be inversely proportional to a large island due to various resource capabilities and limited supporting factors. Mangrove is one of the ecosystems on the coast of a small island that is susceptible to disturbance because it is close to human activities. This study aimed to determine the mangrove ecosystem management strategy on the coast of the Siak Regency. The research was conducted from July to August 2020 using survey and interview methods. Data analysis used the Analytical Hierarchy Process to determine the mangrove management strategy. The results showed that community involvement is a priority for managing sustainable mangrove ecosystems with the assistance of the Government and NGOs. Management priority factors, namely ecology, while still paying attention to economic, social, institutional, and technological concerns.